2019
DOI: 10.1111/jgh.14732
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pancreatic calcification on preoperative computed tomography of intraductal papillary mucinous neoplasms

Abstract: Background and Aim Chronic pancreatitis is a risk factor for pancreatic cancer. Pancreatic calcification is a characteristic of chronic pancreatitis; however, its significance for intraductal papillary mucinous neoplasm (IPMN) oncogenesis remains unknown. Therefore, we investigated the relationship between pancreatic calcification and invasive IPMN. Methods This study included 157 patients who underwent resection for IPMN between April 2001 and October 2016 (intraductal papillary mucinous adenoma, n = 76; noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Previous studies have also reported that the presence of coarse calci cations is associated with high risk for malignancy. [27] Not much is known about PC and malignancy in other non-CP diseases, and some of our results were somewhat contradictory. In MCN, multilocular macrocystic lesions and lesions with calci cations in the wall had a higher risk of malignancy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies have also reported that the presence of coarse calci cations is associated with high risk for malignancy. [27] Not much is known about PC and malignancy in other non-CP diseases, and some of our results were somewhat contradictory. In MCN, multilocular macrocystic lesions and lesions with calci cations in the wall had a higher risk of malignancy.…”
Section: Discussionmentioning
confidence: 61%
“…Calci cation around the pancreatic lesions was de ned as calci cation pushed aside by the lesion and not assessed as intralesional calci cation. [12] (3) Distribution of calci cations -If the calci cations were observed in any particular part of the parenchyma of pancreas such as the uncinate process, head, body, or tail of the pancreas, then it was considered to have segmental distribution while in patients with diffuse distribution the calci cations were located throughout the entire parenchyma of pancreas. [7] (4) Morphology of calci cation -Eggshell calci cations was de ned as linear calcium deposits in the wall or septae.…”
Section: Data Source and Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intralesional calcification was defined as calcification within the lesion, including wall of the cyst, septa, and mural nodules. Calcification around the pancreatic lesions was defined as calcification pushed aside by the lesion and not assessed as intralesional calcification [ 12 ]. (3) Distribution of calcifications—If the calcifications were observed in any particular part of the parenchyma of pancreas, such as the uncinate process, head, body, or tail of the pancreas, then it was considered to have segmental distribution while in patients with diffuse distribution the calcifications were located throughout the entire parenchyma of pancreas [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…“Cyst wall” indicates calcification that was found beside the cyst, and “septum” indicates calcification that was present in the cyst bulkhead. A central calcified scar consisted of calcified septations radiating outwards with a sunburst or stellate appearance called as stellate central calcifications [ 6 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%